2019
DOI: 10.3389/fphar.2019.01186
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Driven Anti-Inflammatory and Anti-Psoriasis Like Efficacies of Nutraceutical Sea Buckthorn (Hippophae rhamnoides) Oil

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by circumscribed, red, thickened plaques with overlying silvery white scales. It is associated with the release of pro-inflammatory mediators that lead to the development of edema and distress. Here we show the anti-inflammatory and anti-psoriatic efficacies of a neutraceutical sea buckthorn oil (SBKT) derived from the fruit pulp of Hippophae rhamnoides. Chemical analysis of the SBKT showed the presence of 16 major saturated, mono-, and polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The present approach for treating free fatty acid (FFA) induced steatosis is limited to the application of thiazolidinediones and fibrates, in combination with lifestyle modifications [ 31 ]. Recent studies have shown that polyherbal formulations have equivalent efficacy to their allopathic counterparts in healing diseases without causing any side effects [ 32 , 33 , 34 ]. Therefore, herbal formulations such as Divya Sarva-Kalp-Kwath (SKK) marketed under its brand name ‘Livogrit’ is considered as an alternative therapeutic intervention against steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present approach for treating free fatty acid (FFA) induced steatosis is limited to the application of thiazolidinediones and fibrates, in combination with lifestyle modifications [ 31 ]. Recent studies have shown that polyherbal formulations have equivalent efficacy to their allopathic counterparts in healing diseases without causing any side effects [ 32 , 33 , 34 ]. Therefore, herbal formulations such as Divya Sarva-Kalp-Kwath (SKK) marketed under its brand name ‘Livogrit’ is considered as an alternative therapeutic intervention against steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The TPA-induced mouse ear skin inflammation model, as described previously, was employed with minor modifications [37,38]. Briefly, 20 µL of TPA solution (125 µg/mL in acetone) was applied topically on the mice ear on days 0, 2, 4, 6, 8, and 10.…”
Section: Generation Of Tpa-induced Psoriasis-like Mouse Modelmentioning
confidence: 99%
“…Anti-psoriatic activity of WSSO was investigated on animals stimulated with TPA. Treatment regime was followed as described for other ayurvedic oil based formulations for skin disorders, where topical application on affected skin was complemented with an oral dose supplement [38][39][40]. Animals were treated with 20 µL topical application WSSO along with 410 or 1230 mg/kg p.o.…”
Section: Generation Of Tpa-induced Psoriasis-like Mouse Modelmentioning
confidence: 99%
“…38,39 3 The nutritional and health effects of SB 3.1 Anti-inammatory and immunomodulatory effects 3.1.1 Anti-inammatory effect. SB extract or preparation as well as the isolated component was found to possess anti-inammatory activity, thus may be used for the prevention or treatment of periodontal inammation, 40 oropharyngeal mucositis, 41 skin inammatory disease, 42,43 endotoxin induced sepsis 44 and allergic symptoms, 45 etc. Isorhamnetin, a avonoid abundant in the fruit of SB, showed a variety of anti-inammatory activities.…”
Section: Vitamin and Mineral Elementsmentioning
confidence: 99%
“…Furthermore, the antipsoriasis-like effect of SB oil was estimated with both in vitro (human monocytic cells) and in vivo oral/topical treatment (TPA-induced CD-1 mice psoriasis-like model). 43 So far, the skin benets of SB were mainly reected in skin care as well as the improvements of some skin lesions.…”
Section: Effect On the Skinmentioning
confidence: 99%